1998
DOI: 10.1046/j.1365-2044.1998.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

The intubating laryngeal maskClinical appraisal of ventilation and blind tracheal intubation in 110 patients

Abstract: SummaryThis study assesses the efficacy of the intubating laryngeal mask as a ventilation device and blind intubation guide. Following induction of anaesthesia with propofol, the device was successfully inserted at the first attempt in 110/110 (100%) patients. Placement took less than 10 s in all patients. Size selection was based on nose-chin distance. Adequate ventilation was achieved in 104/110 (95%) patients. Blind tracheal intubation using an 8-mm internal diameter straight silicone cuffed tracheal tube w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 19 publications
4
31
2
Order By: Relevance
“…This result is consistent with other studies which varied between 89.5-100%. [15][16][17][18] Ease of tracheal intubation using the LMAFastrach ™ was significantly superior to using the air-Q ™ ILA in terms of cricoid manipulation requirement, ease of passage, number of attempts required, and eventual success rate.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This result is consistent with other studies which varied between 89.5-100%. [15][16][17][18] Ease of tracheal intubation using the LMAFastrach ™ was significantly superior to using the air-Q ™ ILA in terms of cricoid manipulation requirement, ease of passage, number of attempts required, and eventual success rate.…”
Section: Discussionmentioning
confidence: 97%
“…[8][9][10][11][12][13][14] Reported success rates of tracheal intubation using the LMA-Fastrach ™ have varied between 89.5-100%. [15][16][17][18] Intubation using the intubating laryngeal mask airway has been associated with lesser adverse cardiovascular responses, compared to conventional intubation with direct laryngoscopy. Fewer incidents of injury to teeth and lips were reported as the laryngoscope was not required.…”
mentioning
confidence: 99%
“…ILMA TM for secondary tracheal intubation: Numerous reports have confirmed the effectiveness of the ILMA TM for both ventilation and blind intubation in patients without airway difficulties [89,[91][92][93][94][95][96][97][98]]. The overall intubation success rate in 1100 patients in these studies was 95.7% [90].…”
Section: Plan B: Secondary Tracheal Intubation Planmentioning
confidence: 94%
“…1,13 Previous studies have reported that, when tracheal intubation was attempted blindly through the intubating laryngeal mask the success rate was high (93-100%). 8,9,14 However, this blind intubation may fail in 50-60% of patients at the first attempt 8,9,14 and might damage the larynx and surrounding tissues, such as impingement of the epiglottis into the laryngeal inlet 15 or perforation of a esophageal pouch. 16 Therefore, caution is required for the blind technique, 17 particularly when there is resistance during the advancement of a tracheal tube or when ventilation via the mask is suboptimal.…”
Section: Discussionmentioning
confidence: 99%